2013
DOI: 10.1371/journal.pntd.0002498
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Acquired Immune Responses to P. vivax Merozoite Surface Protein 3α and Merozoite Surface Protein 9 Are Associated with Reduced Risk of P. vivax Malaria in Young Papua New Guinean Children

Abstract: Background Plasmodium vivax is the most geographically widespread human malaria parasite. Cohort studies in Papua New Guinea have identified a rapid onset of immunity against vivax-malaria in children living in highly endemic areas. Although numerous P. vivax merozoite antigens are targets of naturally acquired antibodies, the role of many of these antibodies in protective immunity is yet unknown.Methodology/Principal FindingsIn a cohort of children aged 1–3 years, antibodies to different regions of Merozoite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 50 publications
4
70
0
1
Order By: Relevance
“…Although PvMSP-3α antibodies appeared to be a marker of P. vivax infection in cross-sectional data from Stanisic et al [36], cohort data from the same study showed a 47% reduction in the risk of symptomatic P. vivax for PvMSP-3α RII IgG responders and around a 20% risk reduction for IgG responders to PvMSP-3α NT , PvMSP-3α RI and PvMSP-3α CT (Figure 6). …”
Section: Cohort Studiesmentioning
confidence: 91%
See 4 more Smart Citations
“…Although PvMSP-3α antibodies appeared to be a marker of P. vivax infection in cross-sectional data from Stanisic et al [36], cohort data from the same study showed a 47% reduction in the risk of symptomatic P. vivax for PvMSP-3α RII IgG responders and around a 20% risk reduction for IgG responders to PvMSP-3α NT , PvMSP-3α RI and PvMSP-3α CT (Figure 6). …”
Section: Cohort Studiesmentioning
confidence: 91%
“…Lima-Junior et al [25] showed around a 60% reduction in the odds of P. vivax infection in IgG responders to PvMSP-3α full-length (MSP-3α FL ), PvMSP-3α NT , PvMSP-3α RI , and around a 35% reduction for PvMSP-3α RII and PvMSP-3α CT compared with non-responders ( Figure 6). Conversely, Stanisic et al [36] showed fold increases of between Figure 5 Forest plot of the association of PvMSP-1 N-terminus IgG responses with Plasmodium vivax outcomes. Estimates represent the estimate of P. vivax infection in IgG responders compared with non-responders.…”
Section: Cross-sectional Studiesmentioning
confidence: 97%
See 3 more Smart Citations